Peran Orang Tua dalam Mendorong Pembiasaan Ibadah Harian Anak Usia Dini: Studi Kasus di Lingkungan KB Istiqomah Mandailing Natal - Nasution, Gelria; Rahman, Mhd Habibu (Innovative: Journal Of Social Science Research, 2025)
This study aims to examine the role of parents in encouraging the habit of daily worship among early childhood children in the Istiqomah Kindergarten (KB Istiqomah) community in Mandailing Natal. The research method used was descriptive qualitative, with data collection techniques through interviews, observation, and documentation. The results indicate that parents act as role models, motivators, and guides in the process of habituating worship, such as prayer, reciting prayers, and greetings. Supporting factors include a religious family environment and good collaboration between parents and schools. Obstacles faced include parental busyness, lack of religious literacy, and the influence of digital media. This study concludes that active parental involvement is crucial in forming early childhood worship habits. Therefore, strong synergy is needed between families and educational institutions to create an environment that supports the development of religious character from an early age.